Pregnancy Outcomes in Marfan Syndrome: A Retrospective Cohort Study - Hassan, Noura; Patenaude, Valerie; Oddy, Lisa; Abenhaim, Haim A. (American Journal of Perinatology, 2015)
Objective Marfan syndrome (MFS) is a rare connective tissue disease with significant risk for adverse cardiovascular outcomes. Our objective was to evaluate pregnancy and cardiovascular outcomes in pregnant women with MFS.Study Design We conducted a population-based retrospective cohort study using the Healthcare Cost and Utilization Project Nationwide Inpatient Sample (HCUP NIS) database from 2003 to 2010. We used unconditional regression analyses to compare maternal and fetal outcomes among pregnancies in women with and without MFS.Results Out of the 7,094,400 births in our cohort, 339 deliveries were to women with MFS. There was one maternal death and six aortic dissections among women with MFS. Births to women with MFS were more likely to be premature, odds ratio (OR) 2.15 (1.60–2.89), have intrauterine growth restricted and small for gestational age infants, OR 2.06 (1.24–3.43). Women with MFS were more likely to deliver by cesarean section, OR 1.91 (1.53–2.38) and were at higher risk of major morbidities including cardiac arrhythmias, OR 10.64 (5.49–20.61) and pneumothorax, OR 51.95 (6.18, 437.10).Conclusion Pregnant women with MFS are at a particularly high risk of adverse pregnancy and cardiovascular events. Preconception counseling should take these risks into consideration and appropriate pregnancy care in tertiary centers should be considered.
Keywords: Marfan syndrome; pregnancy outcomes; maternal morbidity; maternal mortality